A Case Series of Anti-Metabotropic Glutamate Receptor 2 Antibody-Related Diseases with Distinct Neurological Involvement - Zhang Z; Deng X; Guo D; Zhao J; Li J; He F; Yang L; Peng J (ImmunoTargets and Therapy)
Zhanwei Zhang,1 Xiaolu Deng,1 Dandan Guo,1 Jie Zhao,2 Jian Li,2 Fang He,1,3 Lifen Yang,1,3 Jing Peng1,3 1Department of Pediatrics, Xiangya Hospital of Central South University, Changsha, Hunan Province, People’s Republic of China; 2Department of Neurosurgery, Xiangya Hospital of Central South University, Changsha, Hunan Province, People’s Republic of China; 3Clinical Research Center for Children Neurodevelopmental Disabilities of Hunan Province, Changsha, People’s Republic of ChinaCorrespondence: Lifen Yang; Jing Peng, Department of Pediatrics, Xiangya Hospital of Central South University, 87 Xiangya Road, Changsha, Hunan Province, 410008, People’s Republic of China, Email yanglifen7@126.com; pengjing627@126.comBackground: Anti-metabotropic glutamate receptor 2 (mGluR2)-related diseases are rare autoimmune disorders of the central nervous system that primarily affect the cerebellum and are occasionally associated with malignancies.Methods: Data, including demographics, symptoms, blood and cerebrospinal fluid (CSF) tests, and brain magnetic resonance imaging (MRI), were retrospectively collected from two patients with informed consent at Xiangya Hospital from February 2024 to October 2024. Autoantibodies associated with autoimmune encephalitis were tested using cell-based assays. The literature describing anti-mGluR2 antibody-related diseases was searched for in PubMed and five cases were reviewed.Results: Two cases of anti-mGluR2 antibody-related diseases were reported: one with acute cerebellitis and the other with refractory seizures. Brain MRI showed cerebellar involvement in the cerebellitis patient. Anti-mGluR2 antibodies were detected in the serum but not in the CSF of both cases, and both responded well to immunotherapy. A review of five patients (all female, aged 3– 78 years) found four with cerebellar ataxia or cerebellitis and one with immune-related epilepsy. Common symptoms included dysarthria, gait instability, and gaze/nystagmus, while seizures were rare. MRI revealed cerebellar involvement in most cases. Anti-mGluR2 antibodies were present in the serum of all patients but only in the CSF of two. Three patients responded well to immunosuppressive treatment, and two had malignancies.Conclusion: Anti-mGluR2 antibody-related diseases are autoimmune disorders primarily characterized by ataxic manifestations, though seizures may also occur. The effectiveness of immunosuppressive treatment is uncertain and screening for tumors is necessary.Keywords: metabotropic glutamate receptor 2, antibody, cerebellitis, cerebellar ataxia, seizure